Contrast-agent enhancement in ex vivo flat-panel computed tomography of locally advanced laryngeal cancer. (December 2013) - Kroll, Tobias; Sharma, Shachi Jenny; Dreyer, Thomas; Grams, Astrid; Klussmann, Jens Peter; Obert, Martin; Wittekindt, Claus
Abstract Conclusion: Visualization of cartilage invasion in ex vivo laryngectomy specimens was improved by flat-panel volumetric computed tomography (fpvCT) after diffusion of contrast agents. A prospective study to assess the specificity and sensitivity of this new method is warranted. Objectives: Cartilage invasion is a criterion for staging laryngeal squamous cell carcinoma. Contrast-enhanced CT is routinely used for assessing cartilage invasion. However, the sensitivities and specificities given for this method in the literature vary, and there is a need for improvement of this staging method. The objective of our pilot study was to determine cartilage invasion with fpvCT after contrast agent diffusion. Methods: Three patients underwent preoperative CT and total laryngectomy. The excised larynges were immediately scanned with an fpvCT scanner, without contrast enhancement. Additional fpvCT scans were performed after incubation of the larynges in one of three different contrast agents for 24 and 48 h. The results from presurgical conventional scans, fpvCT scans, and histological examination – as the gold standard – were compared. Results: We demonstrated the feasibility of ex vivo contrast enhancement of laryngeal tissues by diffusion, with a subsequent increase in contrast enhancement and improved visualization of cartilage invasion in fpvCT scans. Histology confirmed the fpvCT results.